THE EFFECTIVENESS OF ELECTRONIC MEDIATION AS A RESOLUTION OF DIVORCE CASES IN THE TANJUNGBALAI RELIGIOUS COURTS - Suriani Suriani; Salim Fauzi Lubis; Junindra Martua; Siti Hajar Siregar; Chairanda Al Azmi (Universitas Labuhanbatu, 2024)
To achieve peaceful dispute resolution, the Supreme Court has shifted from a court approach to a legal dispute resolution approach by utilizing electronic media in the current modern era in order to carry out the administration of justice in a simple, fast and low cost manner and as an effort to increase access to justice. has issued Supreme Court Regulation (PerMA) number 3 of 2022 concerning electronic mediation in court. The purpose of writing this article is to determine the effectiveness of electronic mediation in resolving divorce cases at the Tanjungbalai Religious Court using empirical methods, namely research carried out directly or field observations. This research model comes from social science to research social problems and phenomena. This research was conducted at the Tanjungbalai Religious Court, North Sumatra Province. The conclusion of this research is that mediation of divorce cases at the Tanjungbalai Religious Court which is carried out electronically is not yet effective because it is not in accordance with the intent of the issuance of the Supreme Court Regulation concerning Mediation Procedures in court which is carried out using electronic media in accordance with PerMA number 3 of 2022. This is influenced by by several factors including internal and external factorsKeywords: Electronic Mediation; Religious courts; Divorce